2009
DOI: 10.1039/b820742a
|View full text |Cite
|
Sign up to set email alerts
|

Tuned lifetime, at the ensemble and single molecule level, of a xanthenic fluorescent dye by means of a buffer-mediated excited-state proton exchange reaction

Abstract: The photophysical behaviour of the new fluorescein derivative 9-[1-(2-methyl-4-methoxyphenyl)]-6-hydroxy-3H-xanthen-3-one has been explored by using absorption, and steady-state, time-resolved and single-molecule fluorescence measurements. The apparent ground-state acidity constant of the dye determined by both the absorbance and steady-state fluorescence is almost independent of the added buffer and salt concentrations. The excited-state proton exchange reaction around the physiological pH becomes reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 38 publications
(53 reference statements)
4
53
0
Order By: Relevance
“…The tendency of fluorescein and Oregon Green to undergo excited-state proton transfer reactions has been documented [ 16 , 55 ]. If a suitable proton donor or acceptor (such as a phosphate buffer) is present, this can affect the photophysics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency of fluorescein and Oregon Green to undergo excited-state proton transfer reactions has been documented [ 16 , 55 ]. If a suitable proton donor or acceptor (such as a phosphate buffer) is present, this can affect the photophysics.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, we used the minimal amount of acid/base necessary to obtain a given pH, or we used the minimal amount of PBS (Total phosphate concentration = 0.01 M, [NaCl] = 0.137 M, [KCl] = 2.7 mM). In this regard, a phosphate concentration of 10 mM is low, compared to what is generally necessary to affect fluorescein singlet state photophysics [ 55 ]. Furthermore, control experiments using buffered and un-buffered solutions showed no difference in selected photophysical properties at identical pH values.…”
Section: Methodsmentioning
confidence: 99%
“…20 In our aim to find fluorescein derivatives capable of undergoing the characteristic phosphate-mediated ESPT reaction with a single lifetime in the near-neutral pH region, we study the photophysics of 2-Me-4-OMe TG and 2-OMe-5-Me TG in the presence of phosphate buffer in the pH range between 5 and 10. 21,22 The results showed that both undergo the characteristic ESPT reaction, in which the coupled fluorescence decay exhibits a phosphate-sensitive component on the order of nanoseconds and a second component on the order of subnanoseconds, whose value becomes negligible at pH and phosphate concentrations greater than 6.0 and 0.02 M, respectively. In addition, the larger decay time is highly sensitive to the phosphate concentration, while the presence of other ions not involved in the proton-transfer reaction has a negligible effect on the fluorescence decay time.…”
Section: Introductionmentioning
confidence: 97%
“…Our research group has recently concentrated efforts on the development of different FLIM-based intracellular sensors [ 14 , 15 ]. Specifically, our thorough studies on the excited-state proton transfer (ESPT) reactions of xanthene derivatives, mediated by the presence of suitable proton acceptor/donor pairs [ 16 , 17 , 18 ], led us to propose a FLIM methodology and a family of sensors for the intracellular quantification of the total phosphate ions concentration [ 19 , 20 ]. The presence of a suitable proton donor/acceptor, such as the pair H 2 PO 4 − and HPO 4 2− , does promote an inter-molecular proton transfer to the prototropic species of xanthene dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is not a specific feature of phosphate and other pairs can promote the reaction, such as acetate [ 16 , 23 ] and certain amino acids [ 24 ], not all the buffers are capable of promoting the ESPT reaction [ 25 ]. Interestingly, the family of xanthene derivatives so-called Tokyo Green dyes [ 26 ], which have the main feature of an off acidic prototropic form, showed fluorescence decay traces that were mostly mono-exponential when undergoing the buffer-mediated ESPT reaction, and the decay time of such fluorescence kinetics was dependent on the total phosphate concentration [ 17 ]. Based on these results, we started the development of fluorescent phosphate sensors in which the analytical parameter was the fluorescence lifetime of the dye, with particular usefulness for intracellular sensing using FLIM microscopy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%